Water equivalence of a solid phantom material for radiation dosimetry applications. (April 2020) - Gargett, Maegan A.; Briggs, Adam R.; Booth, Jeremy T.
Abstract: Radiological water equivalence of solid phantoms used for radiotherapy is often desired, but is non-trivial to achieve across the range of therapeutic energies. This study evaluated the water equivalence of a new solid phantom material in beam qualities relevant to radiotherapy applications. In-phantom measured depth distributions were compared to that in water to assess the relative attenuation and scatter characteristics of the material. The phantom material was found to be dosimetrically equivalent to water within (1.0 ± 1.0)% for megavoltage photon beam qualities, (1.5 ± 1.3)% for megavoltage electron beam qualities, (1.5 ± 1.5)% for medium-energy kilovoltage X-rays and (3.0 ± 1.5)% for low-energy kilovoltage X-rays.